Analysis of Source Culture in the Current EFL Textbooks in Indonesia - Selli Syah Putri Sihombing; Asnawi (Medan Resource Center, 2023)
The aim of this study was to investigate the culture values represented in an English textbook provided by the Ministry of Education and Culture in terms of the type of culture values represented. This is a qualitative research, the data were collected in the form of the reading passages in the textbook. The illustrations that accompany the text analyzed if it assists the interpretation of the meaning to collect data and data analysis in this research was descriptive analysis in order to reveal what cultures values are represented in the textbook, the contents in the reading passages were categorized into the source culture, the target culture, the international culture. The result of this research was found that there was a significant on the findings and discussion the findings and discussion, it can be concluded that the result from analyzing the text book focus on 45 the reading passages, there are 9% that present source culture (SC), 18% present target culture (TC), 26% present international target culture (IC), and until 47% culture free(CF) dominate the cultural content on the textbook “Interlanguage for Second Grader Students of Junior High School by Joko Priyana”.